2012
DOI: 10.1186/1471-2458-12-469
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of tuberculosis through community-based active case finding in Cambodia

Abstract: BackgroundSince 2005, Cambodia’s national tuberculosis programme has been conducting active case finding (ACF) with mobile radiography units, targeting household contacts of TB patients in poor and vulnerable communities in addition to routine passive case finding (PCF). This paper examines the differences in the demographic characteristics, smear grades, and treatment outcomes of pulmonary TB cases detected through both active and passive case finding to determine if ACF could contribute to early case finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
80
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 10 publications
12
80
0
3
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] India is a low-to middle-income country, with approximately 30% of the population earning below the international poverty line (US$1.25 per day). 10 Despite a well-developed public health system, many populations in India remain either underserved or without access to the health services available from the public health facilities.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] India is a low-to middle-income country, with approximately 30% of the population earning below the international poverty line (US$1.25 per day). 10 Despite a well-developed public health system, many populations in India remain either underserved or without access to the health services available from the public health facilities.…”
mentioning
confidence: 99%
“…This ratio was adjusted by the sensitivity of the GeneXpert MTB/RIF assay in detecting each of these types (76% for smear-negative cases and 98% for smear-positive cases11,12). A previous study of ACF activities in Cambodia found slightly higher mortality rates in PCF cases than in ACF cases 2. We used these data to extrapolate the respective mortality rates for treated smear-positive and smear-negative TB, which resulted in beta distributions with a mean of 2.2% and 0.7% respectively, and with considerable overlap in the two distributions.…”
Section: Methodsmentioning
confidence: 99%
“…4 In the results of the FIDELIS (Fund for Innovative DOTS Expansion through Local Initiatives to Stop TB) project in China, which massively mobilised school students for case finding, the case detection in intervention counties increased by a factor of 3.5 relative to the pre-intervention period. 5 There were some limitations to our study. While our approach demonstrated a potential for improved case detection in the short term, we do not know if these trends are sustainable; we will need to re-examine the results once all the mapped households in the intervention area are covered.…”
Section: Public Health Actionmentioning
confidence: 99%
“…Community-based ICF interventions implemented elsewhere in India and other countries have shown similar results; this reflects the replicability and scalability of such interventions. [3][4][5] An intervention in Orissa, India, increased case detection by 11%. 3 A similar ICF activity conducted in Ethiopia doubled the pulmonary TB case notification rate, from 64 to 127/100 000 population/year.…”
Section: Public Health Actionmentioning
confidence: 99%